2020
DOI: 10.1108/afr-11-2018-0098
|View full text |Cite
|
Sign up to set email alerts
|

The impact of microfinance on Indonesian rural households' welfare

Abstract: PurposeThis study investigates the welfare impact of microfinance on rural households in Indonesia. Its finding will bridge the gap in the Indonesian microfinance literature.Design/methodology/approachThe research was conducted by collecting primary data and administering a structured questionnaire to rural households in Bantul District,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
2
19
0
6
Order By: Relevance
“…Such association is elucidated to be reflective of the ways that financial inclusion is achieved within social settings, such that those with more income are more likely to receive financial assistance. However, the literature on the role of income in shaping CSR expectations and perceptions of the rural household seems to be fragmented with no convincing proofs (Santoso et al, 2020). Although some of the literature suggests that lower income groups give high priority to CSR and carry stronger CSR expectations than people from higher income groups, few studies have attempted to show where high‐income groups and low‐income groups were not found to differ in their CSR perceptions, orientations, and expectations (Corak, 2013; Piprek, 2008).…”
Section: Stakeholder Theory Of Csrmentioning
confidence: 99%
“…Such association is elucidated to be reflective of the ways that financial inclusion is achieved within social settings, such that those with more income are more likely to receive financial assistance. However, the literature on the role of income in shaping CSR expectations and perceptions of the rural household seems to be fragmented with no convincing proofs (Santoso et al, 2020). Although some of the literature suggests that lower income groups give high priority to CSR and carry stronger CSR expectations than people from higher income groups, few studies have attempted to show where high‐income groups and low‐income groups were not found to differ in their CSR perceptions, orientations, and expectations (Corak, 2013; Piprek, 2008).…”
Section: Stakeholder Theory Of Csrmentioning
confidence: 99%
“…To identify the factors affecting the access to microcredit, the present study employed a binary logistic regression model. Binary logistic regression is useful when the dependent variable is dichotomous (Santoso 2016). The general parametric functional expression of this model can be given as follows:…”
Section: Access To Microcreditmentioning
confidence: 99%
“…Findings reliably demonstrate that entry to public lines of lending has a substantial and significant optimistic effect on employment and export growth, while authors have not seen any significant impact on productivity measurement (DeNegri et al, 2011). Santoso et al (2020) conducted research in Bantul district, Indonesia, by gathering primary information and a structured questionnaire was administered to rural families. The logistical model was used by the authors to assess the social effects of microcredit debtors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The logistical model was used by the authors to assess the social effects of microcredit debtors. The study found that monthly income, loan, mensural expenditure, credit amounts, interest rates, marital status and education have major effects on the likelihood of increasing the benefit of borrowers following access to micro-credit (Santoso et al, 2020). The evidence and theory have raised concerns, that microcredit is harmful rather than good, especially when offered at high interest rates.…”
Section: Review Of Literaturementioning
confidence: 99%